Analisis Yuridis Terhadap PP No.6 Tahun 2010 Tentang Satuan Polisi Pamong Praja di Provinsi Kepri - Elza Syarief; Lu Sudirman; Deddy Eka Saputra (Fakultas Hukum, Universitas Internasional Batam, 2017)
Law No. 32 of 2004 on Local Government and Government Regulation No. 6 of 2010 on the Civil Service Police Unit has mandated that Public Protection is obligatory under the authority of both the Provincial and Local Government District and the City. On Government Regulation No. 6 of 2010 on the Civil Service Police Unit that requirements to be appointed as Municipal Police are civil servants, but in the province of Riau Islands Civil Service Police Unit number is still much that is not civil servant status. On Government Regulation No. 6 of 2010 on the Civil Service Police Unit that Article 16 point a that the requirements to be appointed as Municipal Police are civil servants, which Civil Service Police Unit has the task of enforcing local laws, organizing public order and peace and the protection of society, but to carry out this task Municipal Police Units are often contradictory and conflicted with the community. Civil Service Police Unit has the task of helping the head area as Regional Regulatory enforcement to create a serene area conditions, and orderly. Legal remedy solving problems where the Civil Service Police Unit of the police human resources of the Civil Service has had Permendagri 38 of 2010 on the Civil Service Training police, merging function that refers Satlinmas Regulation No. 6 of 2010 on the civil service and police force Regional Government only raised police members of the Civil Service only for the status of Civil Servants.